The Influence of Creative Entrepreneurship Learning Outcomes and Entrepreneurial Motivation on Entrepreneurial Interest of Grade XI Students at SMKN 1 Tengaran - Yuliana, Erika; Saptariana, Saptariana; Kuswardinah, Asih; Astuti, Pudji (Food Science and Culinary Education Journal, 2023)
Abstract. One of the objectives of vocational secondary education is to prepare students to be productive and able to work independently through entrepreneurship. This research was conducted to analyze the influence between PKK learning outcomes and entrepreneurship motivation on students' interest in entrepreneurship. Data collection techniques with documentation and questionnaires were distributed to the sample, namely 246 class XI students of SMKN 1 Tengaran in all majors. The method of analysis using descriptive percentage test and regression test. The results of the descriptive test on the percentage of the PKK learning outcomes variable were in the complete criteria, the variables of motivation and interest in entrepreneurship were in the high category. The results of the regression test found an effect between PKK learning outcomes and entrepreneurship motivation both partially and simultaneously with the equation Y = 49.216 + 0.472 X1 + 0.381 X2, which can be interpreted that PKK learning outcomes have an effect of 47.2% on interest in entrepreneurship and entrepreneurship motivation has an effect of 47.2% 38.1% of interest in entrepreneurship. So after knowing the description of the variable conditions it is suggested that class XI students of SMKN 1 Tengaran together can improve learning outcomes and motivation for entrepreneurship and interest in entrepreneurship so that the goals of vocational high schools (SMK) can be achieved. Keywords: PKK Learning Outcomes, Entrepreneurial Motivation, Interest in Entrepreneurship. Abstrak. Salah satu tujuan pendidikan menengah kejuruan adalah yaitu menyiapkan peserta didik agar produktif dan mampu bekerja mandiri dengan berwirausaha. Penelitian ini dilakukan untuk menganalisis pengaruh antara hasil belajar PKK dan motivasi berwirausaha terhadap minat berwirausaha siswa. Teknik pengumpulan data dengan dokumentasi dan kuesioner yang dibagikan kepada sampel yaitu 246 siswa kelas XI SMKN 1 Tengaran diseluruh jurusan. Metode analisis menggunakan uji deskriptif persentase dan uji regresi. Hasil uji deskriptif persentase variabel hasil belajar PKK berada pada kriteria tuntas, variabel motivasi dan minat berwirausaha pada kategori tinggi. Hasil uji regresi ditemukan pengaruh antara hasil belajar PKK dan motivasi berwirausaha baik secara parsial maupun simultan dengan persamaan Y = 49,216 + 0,472 X1 + 0,381 X2, dimana dapat diartikan bahwa hasil belajar PKK berpengaruh sebesar 47,2% terhadap minat berwirausaha dan motivasi berwirausaha berpengaruh sebesar 38,1 % terhadap minat berwirausaha. Sehingga setelah mengetahui gambaran dari kondisi variabel disarankan untuk siswa kelas XI SMKN 1 Tengaran bersama-sama dapat meningkatkan hasil belajar dan motivasi berwirausaha serta minat berwirausaha agar tujuan sekolah menengah kejurusan (SMK) dapat tercapai. Kata kunci : Hasil Belajar PKK, Motivasi Berwirausaha, Minat Berwirausaha.